The relationship between leadership styles and job satisfaction - Ertekin, Pınar Orpen (My University, 2004)
Name and Surname : Pınar Orpen Ertekin Field: Public Management Proramme: Human Resources Management and Development Supervisor: Yrd. Doç. Dr. Deniz Börü Degree Awarded and Date: Master - July 2004 Leadership, Job satisfaction

THE RELATIONSHIP BETWEEN LEADERSHIP STYLES AND JOB SATISFACTION Leadership has become an important subject with the developments and changes in the new business environment. To adopt to these developments and changes, managers also have to have good leadership traits. Choosing the appropriate leadership style, effects the organizations performance. Meanwhile, the success of the organizations will be possible with happy and satisfied employees, therefore importance of job satisfaction is vital. With this study, the relationship between the new leadership styles namely; transformational and transactional leadership styles and job satisfaction is tried to explain. 114 employees from a firm operating in automotive sector have attended to this research study. With the study, it was seen that, the attendants perceived the leadership styles as a whole and these leadership styles had explanatory effect on the job satisfaction of the attendants. It seems that, the cultural differences effect how the employees perceive their leader's leadership style and their satisfaction may change with this perception. Soyadı : Pınar Orpen Ertekin Kamu Yönetimi Human Resources Management and Development Yrd. Doç. Dr. Deniz Börü Tez Türü ve Tarihi: Yüksek Lisans - Temmuz 2004 derlik, İş Tatmini ÖZET LİDERLİK TARZLARI İLE İŞ TATMİNİ ARASINDAKİ İLİŞKİLER Son yıllarda iş dünyamızda yaşanan değişimler ve gelişmeler, liderlik konusunu gittikçe önemli hale getirmiştir. Bu gelişmelere ve değişimlere uyum sağlayabilmeleri için yöneticilerin aynı zamanda iyi liderlik özellikleri de taşımaları gerekmektedir. Liderlik tarzının uygun seçilmiş olması, organizasyonların performansını etkilemektedir. Organizasyonların başarısı, mutlu ve tatmin olmuş çalışanlarla mümkün olacağından bu aşamada iş tatmininin önemi de devreye girmektedir. Bu çalışma ile yeni liderlik tarzları olarak adlandırılan dönüştürücü ve iş gördürücü liderlik tarzları ile çalışanların iş tatmini arasındaki ilişki anlatılmaya çalışılmıştır. Araştırmaya otomotiv sektöründe faaliyet gösteren bir firmadan 114 çalışan katılmıştır. Araştırma ile, çalışmaya katılan çalışanların, liderlik tarzlarını bir bütün olarak algıladıkları ve bu liderlik tarzlarının da çalışanların iş tatminleri üzerinde açıklayıcı etkisi olduğu sonucuna varılmıştır. Bununla beraber, kültürel farklılıkların da çalışanların liderlerinin davranış tarzlarını farklı algılamalarında rol oynayabileceği ve işten duydukları tatminin de bununla beraber değişebileceği görülmüştür.
Keywords: Liderlik